1992
DOI: 10.1161/01.hyp.20.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of cardiovascular risk factors in confirmed prehypertensive individuals.

Abstract: Numerous studies have indicated that hypertensive subjects have an atherogenic lipoprotein pattern, hyperinsulinemia, and impaired glucose tolerance relative to normotensive individuals. These abnormalities could be due to adverse effects of certain antihypertensive agents, to pathophyslological concomitants of the hypertensive state itself, or to both. In this report, we describe the cardiovascular risk factor profile of 1,440 subjects who were normotensive and were not taking any antihypertensive medications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
100
2
5

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(114 citation statements)
references
References 67 publications
7
100
2
5
Order By: Relevance
“…This is consistent with previous studies in adult populations showing clustering of metabolic abnormalities associated with the development of hypertension. [12][13][14][15] The current data, by showing the highest adverse trends in risk variables of metabolic syndrome among the hypertensive group, suggest that metabolic sequelae of obesity might have been well established much earlier in the hypertensive group versus the prehypertensive group.…”
Section: Srinivasan Et Al Longitudinal Traits Of Youth At Risk For Hymentioning
confidence: 62%
See 1 more Smart Citation
“…This is consistent with previous studies in adult populations showing clustering of metabolic abnormalities associated with the development of hypertension. [12][13][14][15] The current data, by showing the highest adverse trends in risk variables of metabolic syndrome among the hypertensive group, suggest that metabolic sequelae of obesity might have been well established much earlier in the hypertensive group versus the prehypertensive group.…”
Section: Srinivasan Et Al Longitudinal Traits Of Youth At Risk For Hymentioning
confidence: 62%
“…9 -11 Further, prospective studies have shown that hypertension is preceded by a prehypertension stage characterized by abnormalities considered as potential metabolic precursors of hypertension. [12][13][14][15] However, in this regard, the course of concurrent development of adverse levels of blood pressure and other risk variables of metabolic syndrome during the period of childhood, adolescence, and young adulthood in persons at risk still needs elucidation. This might be useful not only in assessing future risk but also in prevention and intervention algorithms.…”
mentioning
confidence: 99%
“…Haffner et at. suggested that the cluster of atherogenic findings (atherogenic lipid and lipoprotein profile, glucose intolerance, and hyperinsulinemia) actually precede the development of the hypertensive state (Haffner et al, 1992). MTHFR gene mutation as an atherogenic risk factor may contribute to development of hypertensive state.…”
Section: Introductionmentioning
confidence: 99%
“…Adjustment for confounding variables, including age and BMI, removed the effect of FPG. Haffner and Ferrannini [23] have also shown that the difference in baseline PLPG between arterial hypertension cases and normotensive subjects disappeared after adding BMI and an index of body fat distribution to the model, a ®nding that was not con®rmed by Selby [24].…”
Section: Discussionmentioning
confidence: 98%